Development of a Direct and Rapid Detection Method for Viable but Non-culturable State of Pediococcus acidilactici - Guan, Yu; Wang, Kan; Zeng, Yang; Ye, Yanrui; Chen, Ling; Huang, Tengyi (Frontiers in Microbiology, 2021)
Pediococcus acidilactici may significantly reduce the pH-value, and thus has different influence, including serving as a probiotic in human microbiota but a spoilage in human food as it could change the flavor. Pediococcus acidilactici is also capable of entering into the viable but non-culturable (VBNC) state causing false negative results of standard culture-based detection method. Thus, development of detection method for VBNC state P. acidilactici is of great significance. In this study, propidium monoazide (PMA) combined with cross priming amplification (CPA) was developed to detect the VBNC cells of P. acidilactici and applied on the detection in different systems. With detection limit of 104 cells/ml, high sensitivity, and 100% specificity, PMA-CPA can successfully detect VBNC cells of P. acidilactici and be applied in with high robustness.